2020
DOI: 10.2298/jsc190329123d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 5Es learning model on the conceptual understanding and science process skills of pre-service science teachers: The case of gases and gas laws

Abstract: The aim of this study was to investigate the effects of using a 5Es learning model on the pre-service science teachers' conceptual understanding and science process skills for "gases and gas laws". The sample of the study consisted 49 pre-service science teachers enrolled for the "Science Laboratory Practices-I" course within the department of science education of a Turkish state university. Through a quasi-experimental research method (pre-and post-test research design), an experimental group was exposed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…Since most of the dependent variables covered transferable and transformable skills (e.g., critical thinking, environmental literacy, decision making, argumentation, and chemical literacy), the research papers seem to have paid more attention to the demands of the 21 st century skills. Meanwhile, although they concentrated on cognitive and affective learning domains (e.g., conceptual understanding, environmental/chemical literacy, attitude, perception, motivation, self-efficacy, and scientific habits of mind) as dependent variables, they have not focused on psychomotor skills that enables students to comprehend the nature and philosophy of science/chemistry (e.g., Irwanto et al, 2019;Karsli Baydere et al, 2020). Interestingly, only one each paper explicitly focused on chemical literacy (Cigdemoglu & Geban, 2015) and scientific literacy (Vogelzan et al, 2020) as a dependent variable.…”
Section: Thematic Codes For the Research Papersmentioning
confidence: 99%
“…Since most of the dependent variables covered transferable and transformable skills (e.g., critical thinking, environmental literacy, decision making, argumentation, and chemical literacy), the research papers seem to have paid more attention to the demands of the 21 st century skills. Meanwhile, although they concentrated on cognitive and affective learning domains (e.g., conceptual understanding, environmental/chemical literacy, attitude, perception, motivation, self-efficacy, and scientific habits of mind) as dependent variables, they have not focused on psychomotor skills that enables students to comprehend the nature and philosophy of science/chemistry (e.g., Irwanto et al, 2019;Karsli Baydere et al, 2020). Interestingly, only one each paper explicitly focused on chemical literacy (Cigdemoglu & Geban, 2015) and scientific literacy (Vogelzan et al, 2020) as a dependent variable.…”
Section: Thematic Codes For the Research Papersmentioning
confidence: 99%
“…Yet while most gases are invisible, people often mistakenly assume that they are weightless. Understanding the microscopic structure relating to atoms and molecules and its relationship to macroscopic properties requires a high degree of abstraction (Demircioglu & Yadigaroglu, 2014;Gabel et al, 1987;Karsli et al, 2020;Pabuccu & Erduran, 2016;Rice, 2005;Tatar, 2011;Yalçınkaya & Boz, 2015). Therefore, it is a source of inadequate knowledge as can be seen from this example as well as other items in our CKT.…”
Section: Lack Of Content Knowledgementioning
confidence: 99%
“…Studies have shown that misconceptions about the state of matter exist at all levels of learners. Thus, even in the third year of college study and after a few courses in the sciences, pre-service STs still hold misconceptions about the state of matter (Ayas et al, 2010;Karsli, Ayas & Çalik. 2020;Özmen & Naseriazar, 2018).…”
Section: Difficulties In Acquiring Content Knowledge About States Of Mattermentioning
confidence: 99%
“…Akıllı biçimlendirici değerlendirme sistemi öğretmenlere öğrencilerin dikkatini çekme, derse aktif katılımını sağlayamaya, öğrenme stil ve zekâ yapılarına uygun materyal ve yöntem seçmelerine yardımcı olmak amacıyla hazırlanmıştır. Öğretmenler her ne kadar mükemmel öğretici olsalar bile bütün öğrenciler aynı şekilde öğrenememekte olduğu düşüncesi dikkate alındığında (Bayrak, Çalık & Doğan, 2019;Bodner, 1990;Karslı & Ayas, 2013;Karsli Baydere, Ayas & Çalik, 2019), akıllı biçimlendirici değerlendirme sisteminin bireysel farklıklara, öğrenme stil ve zeka yapılarına göre materyal, yöntem veya öneride bulunmasının öğrencilerin kendi bilgilerini yapılandırmalarında aktif rol almalarını sağladığı ve öğrenmeyi kolaylaştırdığı söylenebilir. Nitekim uygulama öğretmenlerinin sistemi kullanmaya başladıktan sonra öğrenci alternatif kavramlarını daha çok dikkate almaları ve daha çok bireysel öğretim yöntemlerine yönelmeleri de bu durumun bir göstergesi olarak görülebilir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified